2021
DOI: 10.3390/nu13103315
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic-Induced Gut Microbiota Dysbiosis Damages the Intestinal Barrier, Increasing Food Allergy in Adult Mice

Abstract: (1) Background: The use of antibiotics affects the composition of gut microbiota. Studies have suggested that the colonization of gut microbiota in early life is related to later food allergies. Still, the relationship between altered intestinal microbiota in adulthood and food allergies is unclear. (2) Methods: We established three mouse models to analyze gut microbiota dysbiosis’ impact on the intestinal barrier and determine whether this effect can increase the susceptibility to and severity of food allergy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
45
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(48 citation statements)
references
References 70 publications
(83 reference statements)
3
45
0
Order By: Relevance
“…20 Antibiotic intake by adult mice increases FA susceptibility and severity due to higher intestinal permeability and dysbiosis of the gut microbiota. 4 Another study has shown that feces from healthy infants transplanted into germ-free mice can prevent cow milk allergy. 21 Therefore, it is reasonable to hypothesize that fucoxanthin may prevent FA by enhancing the intestinal epithelial barrier and microbial regulation pathways.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…20 Antibiotic intake by adult mice increases FA susceptibility and severity due to higher intestinal permeability and dysbiosis of the gut microbiota. 4 Another study has shown that feces from healthy infants transplanted into germ-free mice can prevent cow milk allergy. 21 Therefore, it is reasonable to hypothesize that fucoxanthin may prevent FA by enhancing the intestinal epithelial barrier and microbial regulation pathways.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Food allergy (FA) is an adverse immune reaction that occurs when people are exposed to certain foods and can be divided into IgE-mediated or non-IgE-mediated reactions. , It is widely accepted that the FA is associated with immunological abnormalities, inflammatory mediator expansion, increased intestinal permeability, and gut microbiota dysbiosis. However, current immunotherapy treatment (oral immunotherapy, sublingual immunotherapy, and epicutaneous immunotherapy) and medication remain limited and can produce various adverse effects. , Therefore, natural anti-FA substances have attracted significant attention due to their milder effect, fewer side effects, and safety. , …”
Section: Introductionmentioning
confidence: 99%
“…Indeed, it was shown in mice that antibiotic-associated reduction in intestinal microbiota and metabolic abundance such as short-chain fatty acids and tryptophan resulted in an increase in inflammatory response as evidenced by elevated immunoglobulins IgE and IgG1 after sensitization. Upon re-exposure to the allergens, the mice showed evidence for damaged intestinal barrier such as ruptured intestinal villi and a decrease in tight junction proteins ( 66 ). Thus, excessive or irresponsible use of probiotics, many of which are phenotypically resistant to clinically important antibiotics and harbor resistance genes on mobile genetic elements, could further exacerbate the current public health crisis especially in the clinical settings where those with underlying health conditions are most vulnerable.…”
Section: Discussionmentioning
confidence: 99%
“…A food allergen challenge induced a rapid degradation of intestinal intercellular junction proteins, including claudin-1, in a mouse model of food allergy ( 126 ). Downregulation of CLDN1 expression level in the GI tract was also associated with an increased serum IgE level ( 127 ).…”
Section: Evaluation Of the Hypothesismentioning
confidence: 99%